Novel activators and small-molecule inhibitors of STAT3 in cancer. (October 2019) - Yang, Lehe; Lin, Shichong; Xu, Lingyuan; Lin, Jiayuh; Zhao, Chengguang; Huang, Xiaoying
Graphical abstract: Highlights: Novel activators of STAT3 have diverse functions in regulating cancer cellular processes and have been validated as potential drug targets. STAT3 activation is a resistance mechanism. STAT3 inhibitors that show promise as new therapeutic leads can combined with chemotherapies to improve patient outcomes. Abstract: Excessive activation of signal transducer and activator of transcription 3 (STAT3) signaling is observed in a subset of many cancers, making activated STAT3 a highly promising potential therapeutic target supported by multiple preclinical and clinical studies. However, early-phase clinical trials have produced mixed results with STAT3-targeted cancer therapies, revealing substantial complexity to targeting aberrant STAT3 signaling. This review discusses the diverse mechanisms of oncogenic activation of STAT3, and the small molecule inhibitors of STAT3 in cancer treatment.